Nanoparticle size and surface chemistry effects on mechanical and physical properties of nano-reinforced polymers: The case of PVDF-Fe3O4 nano-composites - Francisco Sebastian Navarro Oliva; Mehdi Sahihi; Luc Lenglet; Alejandro Ospina; Erwann Guenin; Andres Jaramillo-Botero; William A. Goddard, III; Fahmi Bedoui (Polymer Testing, 2023)
In the present work, PVDF - Fe3O4 nanoparticle (NP) nanocomposite films were produced using the electrospinning method. We investigated the effect of NP size on the film's morphology (fiber size), mechanical properties, and physical properties (β-phase percentage). Surprisingly, while nanoparticle size acts as an enhancer for mechanical properties, it appeared to act as an inhibitor in terms of its effects on the crystallization of the β-polymorph. This result seemed in discordance with many previous results. A focus on local interactions between the NP surface chemistry and PVDF chains revealed the influence of grafted ligands at the nanoparticle surface on the crystallization of the piezoelectric phase of PVDF. The results from the molecular dynamics (MD) simulations for systems of PVDF chains with slabs of –OH and oleic acid-grafted magnetite, showed that the probability of beta phase configuration decreases when the nanoparticles are functionalized with oleic acid and becomes more probable for –OH terminated magnetite. These computational results are in accordance with our experimental results. To verify this hypothesis, we prepared films with washed nanoparticles to eliminate the excess oleic acid that acts as a β-polymorph inhibitor. As a result, the amount of β-phase obtained for washed nanoparticles increased and the difference in the amount of β-phase between the different samples decreased. Moreover, when heated, the films of nanocomposite with washed NP developed more β-phase for smaller sizes of nanoparticles. At 140 °C, isomerization occurred, and oleic acid was converted into elaidic acid, reducing the steric hindrance, and promoting the interaction between PVDF chains and the surface of the nanoparticles. This isomerization reaction seems to be an enhancer of the α- to β-phase transition. Our results prove that optimizing multiple properties in nano-reinforced polymers requires consideration of different aspects, such as NP size, surface chemistry, and processing methods.Our results based on mixed experimental and modeling approach proved the usefulness of simulation in understanding and guiding our experimental results. Our results suggest that for enhancing piezoelectric properties in PVDF magnetite nano-composites, the chemistry and the molecular morphology of the grafted ligands when combined with NP size could lead to multi-properties enhancement simultaneously.